2015
DOI: 10.1118/1.4924289
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐J‐203: Investigation of 1.5T Magnetic Field Dose Effects On Organs of Different Density

Abstract: Purpose: For the combined 1.5T/6MV MRI‐linac system, the perpendicular magnetic field to the radiation beam results in altered radiation dose distributions. This Monte Carlo study investigates the change in dose at interfaces for common organs neighboring soft tissue. Methods: MCNP6 was used to simulate the effects of a 1.5T magnetic field when irradiating tissues with a 6 MV beam. The geometries used in this study were not necessarily anatomically representative in size in order to directly compare quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our measured dose maps of the ERE are qualitatively consistent with previous phantom measurements and Monte Carlo simulations (Raaijmakers et al 2005, 2008, Lee et al 2015. A region of enhanced dose was observed in the higher density material just before the intersection with the lower density material, and a region of reduced dose was observed in the lower density material just before the boundary with the higher density material.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our measured dose maps of the ERE are qualitatively consistent with previous phantom measurements and Monte Carlo simulations (Raaijmakers et al 2005, 2008, Lee et al 2015. A region of enhanced dose was observed in the higher density material just before the intersection with the lower density material, and a region of reduced dose was observed in the lower density material just before the boundary with the higher density material.…”
Section: Discussionsupporting
confidence: 88%
“…Two Monte Carlo studies that specifically looked at the lung-soft tissue interface also reported hot and cold spots of higher magnitude than measured in the current report. Raaijmakers et al (2008) and Lee et al (2015) measured hot spots of 49% and 46.5%, respectively, and cold spots of 36% and 39.4%, respectively, in Monte Carlo simulations with a 1.5 T field. The discrepancy between these results and the current study may be explained by the fact that the average CT numbers measured for the low-density gels are slightly higher than mean values for healthy lung tissue reported in the literature (typically around −700 to −800 HU) (Biernacki et al 1997, Shin et al 2011, Cressoni et al 2014, Ohkubo et al 2016.…”
Section: Discussionmentioning
confidence: 97%